COMPARATIVE STUDY OF INTERACTION OF SOME DOMESTIC HUMAN INSULIN SUBSTANCES AND ITS ANALOGUES WITH INSULIN RECEPTOR BY METHOD OF SURFACE PLASMON RESONANCE - I. N. Urakova; K. L. Kryshen; O. N. Pozharitskaya; M. V. Gavrilin; A. N. Shikov; M. N. Makarova; V. G. Makarov (Разработка и регистрация лекарственных средств, 2019)
The high demand for insulin preparations by the population of the country makes it urgent to create domestic bioanalogues for the treatment of diabetes mellitus. The equivalency of the quality, safety and efficacy of the bioanalogue with the reference medicinal preparation registered in Russia is required by authority at the stage of preclinical studies. The aim of the study was to study the interaction of insulin substances of domestic production, including short and long-acting insulin with the insulin receptor in comparison with the reference substances registered in Russia by the surface plasmon resonance method. Comparing the interaction kinetics curves and calculated dissociation constants determined by the surface plasmon resonance method it was confirmed that there are no statistically significant differences between the potentially bioanalogical insulin substances Rosinsulin R, Rosinsulin Glargin and Rosinsulin Aspart (LLC ”Zavod Medsintez”, Russia) and the corresponding substances of registered in Russia medicines.